N‐type in‐situ doping effect on vapour‐liquid‐solid silicon nanowire properties for gas sensing applications. Issue 2 (3rd February 2014) - Pichon, L.; Rogel, R.; Jacques, E.; Salaun, A. C.
Abstract N‐type in‐situ doped SiNWs based resistors are fabricated and used as gas (ammonia) sensors. SiNWs are prepared by vapour‐liquid‐solid method (VLS) using gold as catalyst. In‐situ doping level is adjusted by varying the phosphine to silane mole ratio. Because SiNWs can act as sensitive units specific design is developed to allow large sensing areas, following a process fabrication compatible with a mass production planar layout. SiNWs doping effect on ammonia detection is carried out under controlled ammonia/nitrogen mixture varying from 2 ppm to 700 ppm. Results highlight that the relative response, Sg=(I0‐Ig)/I0, where I0 and Ig are the current values in vacuum and reactive ambient respectively, follows a linear behaviour. The relative sensitivity, (S=ΔSg/Δ[NH3]) decreases, whereas the sensitivity (SxI0) increases with the increase of the VLS SiNWs doping level. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)